Java™ for ColdFusion® Developers - Hewitt, Eben (Pearson, 2003)
The first Java guide specifically for experienced ColdFusion developers and Web professionals! Leverage your Web and ColdFusion skills to develop powerful Java applications Master JSP, servlets, custom tags, JavaBeans, JDBC, and other key Java Web technologies Install and run Apache Tomcat 4 and JRun 4 application servers Build several complete applications, including an e-commerce site Includes handy Java glossary and JSP/servlet references Up-to-the-minute coverage of Java 1.4, JSP 1.2, servlet 2.3, and ColdFusion MX With ColdFusion MX and this book, any Web professional can leverage the power of Java to build robust, high-performance Web applications. Leading Web developer and columnist Eben Hewitt begins with a rapid-fire introduction to Java that builds on what you already know about ColdFusion to teach you exactly what you need to know about Java programming. Hewitt's focused examples, real-world insights, and code will take you from the basics of object-oriented programming to sophisticated JSP/servlet development, XML-based applications, and beyond! Master object-oriented application design and programming Build powerful servlets, JavaServer Pages, applets, and desktop applications Leverage XML and XSLT, exception handling, I/O, JDBC databases, and more Understand the similarities and key differences between CFML and Java development Integrate ColdFusion MX with J2EE and servlet technology Create JSP custom tags and use the brand-new JSP Standard Tag Library Includes complete references to JSP tags and the Servlet API, plus a handy Java glossary The bookÕs extensive code examples (downloadable from www.corecoldfusion.com) include a start-to-finish Java e-commerce application.